Language, Identity and symbolic culture - Evans, David (Bloomsbury Academic, 2018)
Language is integral to the construction of personal, socio-cultural and socio-political identities. Language, Identity and Symbolic Culture closely investigates the relationship between language and identities, offering a comprehensive yet progressive view of how linguistics relates to development and education, both in theoretical and real world applications. Progressing from a theoretical core examining the connection between language and individual identity, this book moves on to look at the wider socio-political discourse involving the marginalization and resistance of communities in the world. Beginning with the philosophical paradigms of language, Evans questions whether language shapes personal identities in its daily use or whether language is simply a tool for describing, rather than creating, the world. Extrapolating on this, the contributors utilize case studies from across the globe to see how these linguistic perspectives are played out in the real world, considering the role of language in issues surrounding power, colonization, marginalization and education. Language, Identity and Symbolic Culture offers a view of language identity conflicts around the world and an understanding of the opportunities of political and cultural emancipation created through language and open discourse
Keywords: Discourse analysis; Language Arts & Disciplines; Philosophy; Philosophy of language; Sociolinguistics